2019
DOI: 10.1007/s10663-019-09459-0
|View full text |Cite
|
Sign up to set email alerts
|

The wage premium from foreign language skills

Abstract: The globalisation of labour markets makes language skills one of the key competences required by employers nowadays. The purpose of this paper is to estimate the wage premium from the foreign language skills earned by Poles. Poles seem to be a good case study, because the Polish language is not used for international communication and as many as 58% of Poles command at least one foreign language. I use data from three waves (2012–2014) of the Human Capital Balance survey with a pooled sample of about 35,000 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…In line with Guo and Sun (2014), English proficiency had a significant impact on college students' starting salaries. This might have been predicted: as noted by Liwinski (2019) and by Rozhkova and Roshchin (2019), the impact of English language proficiency is heightened in countries where English is not the dominant language. However, another factor with particular relevance in China is that higher English ability increases students' chances of working in overseas companies, where average salaries can be much higher (Liu et al , 2004).…”
Section: Discussionmentioning
confidence: 96%
“…In line with Guo and Sun (2014), English proficiency had a significant impact on college students' starting salaries. This might have been predicted: as noted by Liwinski (2019) and by Rozhkova and Roshchin (2019), the impact of English language proficiency is heightened in countries where English is not the dominant language. However, another factor with particular relevance in China is that higher English ability increases students' chances of working in overseas companies, where average salaries can be much higher (Liu et al , 2004).…”
Section: Discussionmentioning
confidence: 96%
“…While speaking English (in non-English speaking countries) and German (in non-German speaking countries) seems to have a larger impact on average on employment outcomes, speaking French, Spanish and Italian appears to have positive impacts on employment outcomes for the non-migrant population in many European countries. The differentials due to multilingualism have also been studied in the context of the Turkish (Di Paolo & Tansel 2015), Polish (Liwiński 2019) and German (Stöhr 2015) labour markets. Knowledge 20 Note that 'native population' here refers to the non-migrant population of a country.…”
Section: Multilingualism and Labour-market Outcomesmentioning
confidence: 99%
“…For the People's Republic of China, the estimated wage premium from good knowledge of English is about 30% (Asadullah & Xiao, 2019). For Poland, Liwiński (2019) found that advanced command of a foreign language increases wages by 11%. A higher wage premium was related to the knowledge of Spanish (32%) and French (22%) than English (11%).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Mastering foreign languages, apart from the fact it gives an advantage in recruitment to subsequent educational stages, is extremely valuable on the labour market. Research shows that the command of foreign languages among native employees is associated with higher earnings (Asadullah & Xiao, 2019;Di Paolo & Tansel, 2015;Liwiński, 2019). There is also a belief among Polish parents that it is difficult to learn a foreign language at school.…”
Section: Introductionmentioning
confidence: 99%